Economics and Catholic Social Teaching: A Pedagogy of Navigating Rationality, Self-Interest, Altruism, and Reciprocity - Sescon, Joselito T (Archīum Ateneo, 2022)
This paper proceeds from the tradition of Catholic social teaching (CST) in dialogue with the development of the economy and society; beginning with the advent of modern industrial society. The main research problem is the perceived irreconcilability of the neoclassical microeconomic model of rational self-interested individuals with that of the altruistic and sacrificing behavior that is called for by St. Ignatius; and the Christian church in general. The inspirational challenge to confront this research problem is in the context of teaching economics in Ateneo de Manila University; a Jesuit and Catholic university where Ignatian values and teaching pedagogy are consciously promoted. This paper also progresses from the internal dialogue within the economics discipline on the differing views on self-interest versus the larger interest of society. Economic theory and application have arduously grappled with these two conflicting but assiduously overlapping pursuits of human interests. The paper concludes for the development of separate teaching materials in understanding rationality; self-interest; altruism; and reciprocity. The discussion needs to be discussed in the context of market transactions; state intervention; and building trust and cooperation in communities. It is inevitable to expand to ethics and morality which will then be the natural ground for extension to the social values taught in theology of Catholic social vision. Lastly; the authors recommend that above tradition be pursued through continuing immersion and study on Ignatian spirituality; and the constant dialogue between economics and the theology departments; along with other disciplines in humanities; social sciences; management studies; and the natural sciences.